Colonial/Orientalist Discourse in Western Campaign against Qatar 2022 World Cup - Bennis, Mohammed; Aammari, Lahoucine (International Journal of Language and Literary Studies, 2023)
The image of Muslims in Western media has always been systematically tainted by virulent stereotypes, vituperating ideologies, and fallacious (mis)representations that manifestly echo how power relations regulate Western media's political agenda. Despite intermittent calls for inter-faith and civilization dialogue, orientalist and discursive practices about Muslims still persist which undeniably confirm that Eurocentrism is still haunting Western consciousness, exacerbating further the cultural and epistemological gap between East and West. The process of othering Muslims through Western media texts, narratives, and cartoons is blatant evidence of Western hegemony that seeks to freeze the Orient/Muslims in a permanent state of lethargy and disseminate Western assumed superiority. Western consciousness has been structured to internalize and normalize the superiority and the centeredness of the West, relegating at the same time the Orient to a peripheral position. In this context, the recent event of the FIFA World Cup 2022 held in Qatar is groundbreaking evidence of the continuity of Orientalism. Qatar, the Arab and Muslim nation, has been the target of a vitriolic Western campaign that churns out the same colonial stereotypes about the Orient, being represented as the land of desert corruption, ignorance and uncouthness, hence unfit for Western standards of democracy and human rights. It is, therefore, morally incumbent on the West only to hold such a prestigious event as the World Cup! It is the West’s duty to civilize the backward other! The echo of the infamous “mission civilisatrice” is still looming over! This paper seeks, therefore, through a postcolonial perspective, to expose, analyze, and debunk Western media discourse/campaign on Qatar World Cup by delving into selected samples of newspaper articles and cartoons.